POLA PENGELUARAN PANGAN RUMAH TANGGA MENURUT TINGKAT KETAHANAN PANGAN DI PROVINSI JAWA TENGAH - Purwaningsih, Yunastiti; Hartono, Slamet; Masyhuri, Masyhuri; Mulyo, Jangkung Handoyo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2010)
This research analyzes the system of food expenditure based on the household food security level in Central Java. The household food security levels are classified into four levels, consisting of food-secure, food-less secure, food-vulnerable and food-insecure. The data used are the Susenas data in the form of raw data. The results show that there are significant differences in the proportion of food expenditure among the households of food-secure and food-less secure to the households of food-vulnerable and food-insecure. In each level of household food-secure, household expenditure on instant foods and drinks shows the highest proportion compared to other food groups. The more insecure foods in a household, the higher expenditure proportion for tobacco. In each household group based on the level of food-secure, the households in urban areas have a smaller proportion of rice expenditure compared to the households in rural areas. Based on these results, hopefully the handling priority for the foodsecure problem should be better given to the household groups of food-vulnerable and foodinsecure.